2017
DOI: 10.1177/1010428317719272
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-induced SULT1A3/4 promotes EMT and cancer stemness in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma has the second highest incidence rate among malignant cancers in China. Hepatocellular carcinoma development is complex because of the metabolism disequilibrium involving SULT1A3/4, a predominant sulfotransferase that metabolizes sulfonic xenobiotics and endogenous catecholamines. However, the correlation between SULT1A3/4 and hepatocellular carcinoma progression is unclear. By utilizing immunofluorescence and immunohistochemical analysis, we found that in nine hepatocellular carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…EMT is characterized by the transformation of cell phenotype from epithelial to mesenchymal cells. Various epithelial and mesenchymal markers such as VI, N-cad and E-cad, Slug, Snail and Twist1 are associated with tumor progression [25,26]. In our study, overexpression of AQP9 reduced the invasion and migration activity of HCC cells by down-regulating E-cad and upregulating N-cad and α-SMA, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…EMT is characterized by the transformation of cell phenotype from epithelial to mesenchymal cells. Various epithelial and mesenchymal markers such as VI, N-cad and E-cad, Slug, Snail and Twist1 are associated with tumor progression [25,26]. In our study, overexpression of AQP9 reduced the invasion and migration activity of HCC cells by down-regulating E-cad and upregulating N-cad and α-SMA, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…cells were homogenized and sonicated in RIPA buffer (Sigma-Aldrich; Merck KGaA) on ice. Western blotting was conducted according to our previous report (23). determination of protein content: a small amount of the supernatant was taken with a pipette, and the absorbance was measured by a visible spectrophotometer at a wavelength of 590 nm according to the Bradford method.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Just one previous study discloses that ITGA7 promotes OSCC cell migration and invasion, more importantly, ITGA7 also induces EMT in OSCC [5]. Meanwhile, EMT is not only a well-coordinated process touched off by multiple signaling pathways during embryonic development, but also a kind of pathological characteristic in neoplasia and fibrosis, which has been considered as an essential regulator linked to tumor progression and tumor metastasis through accelerating cancer cell invasion and dissemination to distant organs [18][19][20][21]. In order to explore whether ITGA7 influenced EMT in HCC, we further detected E-cadherin and α-SMA expressions, and we found that ITGA7 knockdown increased E-cadherin expression while decreased α-SMA expression in HCC cells.…”
Section: Discussionmentioning
confidence: 99%